2016
DOI: 10.3892/ijmm.2016.2477
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Lycii Radicis Cortex on RANKL-induced osteoclast differentiation and activation in RAW 264.7 cells

Abstract: Post-menopausal osteoporosis is a serious age-related disease. After the menopause, estrogen deficiency is common, and excessive osteoclast activity causes osteoporosis. Osteoclasts are multinucleated cells generated from the differentiation of monocyte/macrophage precursor cells such as RAW 264.7 cells. The water extract of Lycii Radicis Cortex (LRC) is made from the dried root bark of Lycium chinense Mill. and is termed 'Jigolpi' in Korea. Its effects on osteoclastogenesis and post-menopausal osteoporosis ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 41 publications
2
45
0
Order By: Relevance
“…Osteoclasts are multinucleated, terminally differentiated cells found in bone tissues, which are difficult to culture in vitro, while in recent years, RANKL has been widely and successfully used to induce the differentiation and maturation of osteoclast precursors into osteoclasts (Kim et al, ; Wang, Zheng, et al, ). Therefore, we used RANKL to induce osteoclastogenesis of RAW264.7 cells and BMMs in vitro, and our results revealed that IL‐7 significantly up‐regulated the expression of IL‐7R and activated the c‐Fos/c‐Jun signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoclasts are multinucleated, terminally differentiated cells found in bone tissues, which are difficult to culture in vitro, while in recent years, RANKL has been widely and successfully used to induce the differentiation and maturation of osteoclast precursors into osteoclasts (Kim et al, ; Wang, Zheng, et al, ). Therefore, we used RANKL to induce osteoclastogenesis of RAW264.7 cells and BMMs in vitro, and our results revealed that IL‐7 significantly up‐regulated the expression of IL‐7R and activated the c‐Fos/c‐Jun signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Sex hormones influence body fat distribution and adipocyte differentiation. Some researchers have reported that an estrogen deficiency may be an important obesity-triggering factor [ 44 ], and several studies have reported that estrogen deficiency increases the body weight of mice [ 45 , 46 , 47 ]. In the present study, we showed that the administration of TSG effectively inhibited weight gain by estrogen deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that TSG may prevent disease associated with increased body weight in postmenopausal women. Moreover, estrogen deficiency induces atrophy of the uterus, and uterine atrophy is evidence of the success of ovariectomy [ 45 ]. In the present study, we demonstrated that TSG reduced uterine atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…It was generally used to treat lung fever, cold blood, help reduce blood pressure, etc17. The crude extract of Cortex lycii radicis has growth inhibition effect on GBM cells (U87MG)16.…”
mentioning
confidence: 99%